V for Vendetta - McTeigue, James; Portman, Natalie, 1981-; Weaving, Hugo, 1960-; Rea, Stephen; Fry, Stephen, 1957-; Hurt, John, 1940-2017; Biddle, Adrian; Marianelli, Dario; Warner Home Video (Firm) (Burbank, Calif. : Warner Home Video, 2006)
Set against the futuristic landscape of totalitarian Britain, the story is about a young working-class woman, Evey, who is rescued from a life-and-death situation by a masked man known only as 'V.' Incomparably charismatic and ferociously skilled in the art of combat and deception, 'V' ignites a revolution when he urges his fellow citizens to rise up against tyranny and oppression. As Evey uncovers the truth about 'V's' mysterious background, she also discovers the truth about herself. She becomes his ally in his plan to bring freedom and justice to a cruel and corrupt society.
Title from container.
Full screen.
Director of photography, Adrian Biddle ; editor, Martin Walsh ; music, Dario Marianelli ; costume designer, Sammy Sheldon ; production designer, Owen Paterson.
Natalie Portman, Hugo Weaving, Stephen Rea, Stephen Fry, John Hurt, Tim Pigott-Smith, Rupert Graves, Roger Allam, Ben Miles, Sinéad Cusack.
MPAA rating: R; for strong violence and some language.
DVD; Dolby Digital 5.1 surround, DVD-9, dual-layer.
Keywords: Vendetta -- England -- Drama; Deception -- Drama; Totalitarianism -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Action and adventure films; Science fiction films; Films for the hearing impaired; Suspense films; Science fiction films